Evaluating a Representational State Transfer (REST) Architecture - Costa, Bruno; Pires, Paulo (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2015: Anais do XXVIII Concurso de Teses e Dissertações, 2015)
The use of Representational State Transfer (REST) as an architectural style for integrating services and applications brings several benefits, but also poses new challenges and risks. Particularly important among those risks are failures to effectively address quality attribute requirements such as security, reliability, and performance. An architecture evaluation can identify and help mitigate those risks. In this work we present guidelines to assist architecture evaluation activities in REST-based systems. These guidelines can be systematically used in conjunction with scenario-based evaluation methods to reason about design considerations and trade-offs. This work also present the results of a survey conducted with industry specialists who have performed architecture evaluations in real world REST-based systems in order to gauge the suitability and utility of the proposed guidelines.